GOTHIC simulations of OECD/NEA THAI multi-vessel hydrogen deflagration tests. (January 2021) - Lebel, Luke; Liang, Zhe
Highlights: GOTHIC simulation of hydrogen deflagrations in the THAI vessel. Deflagration in single or multiple volumes under quiescent or turbulent environments. Application of a global burn enhancement factor to account for flame instabilities. Abstract: This paper presents GOTHIC analyses of hydrogen deflagration tests performed in the framework of the OECD/NEA THAI program. The experiments were performed in one or two interconnected vessels under similar conditions, including cases with forced convection loops and both upward- and downward-propagating burns. To capture the influence of initial turbulence and flame wrinkling, a global burn enhancement factor was employed in the calculations. The simulations captured the overall propagation of the hydrogen burns and the pressurization rate. Overall agreement was reasonably good for the upward-propagating flames, but some dynamics in the second interconnected vessel were more challenging for GOTHIC to replicate, as the flame propagation speed was generally over-predicted with the global burn enhancement model. The benchmark exercise has helped to better understand the requirements for modeling hydrogen deflagrations in multiple interconnected volumes with initial turbulence, and can be used to improve guidance on hydrogen issues in nuclear safety analysis.